Preclinical immunogenicity and safety of the cGMP-grade placental malaria vaccine PRIMVAC - Chêne, Arnaud; Leroy, Odile; Havelange, Nicolas; Viebig, Nicola (EBioMedicine, 2019)
Background - VAR2CSA is the lead antigen for developing a vaccine that would protect pregnant women against placental malaria. A multi-system feasibility study has identified E. coli as a suitable bacterial expression platform allowing the production of recombinant VAR2CSA-DBL1x-2x (PRIMVAC) to envisage a prompt transition to current Good Manufacturing Practice (cGMP) vaccine production. - Methods - Extensive process developments were undertaken to produce cGMP grade PRIMVAC to permit early phase clinical trials. PRIMVAC stability upon storage was assessed over up to 3years. A broad toxicology investigation was carried out in rats allowing meanwhile the analysis of PRIMVAC immunogenicity. - Findings - We describe the successful cGMP production of 4.65g of PRIMVAC. PRIMVAC drug product was stable and potent for up to 3years upon storage at −20°C and showed an absence of toxicity in rats. PRIMVAC adjuvanted with Alhydrogel® or GLA-SE was able to generate antibodies able to recognize VAR2CSA expressed at the surface of erythrocytes infected with different strains. These antibodies also inhibit the interaction of the homologous NF54-CSA strain and to a lower extend of heterologous strains to CSA. - Interpretation - This work paved the way for the clinical development of an easily scalable low cost effective vaccine that could protect against placental malaria and prevent an estimated 10,000 maternal and 200,000 infant deaths annually. - Fund - This work was supported by a grant from the Bundesministerium für Bildung und Forschung (BMBF), Germany through Kreditanstalt für Wiederaufbau (KfW) (Reference No: 202060457) and through funding from Irish Aid, Department of Foreign Affairs and Trade, Ireland.